Riskometric assessment of factors affecting population health in situational analysis features of cytochemical indicators of activity circulating and tissue leukocytes and oxidative stress as a factor of chronic inflammation - Sokolovska, I.; Kutsak, A.; Gordienko, L.; Bulanov, V.; Hryshyna, T.; Zarytska, V.; Plakhotnik, O.; Semeniv, I.; Kotuza, A.; Zazirnyi, I.; Kmetyuk, Y.; Kovtun, R.; et al. (My University, 2020)
The study of the mechanism of oxidative stress and regulation of oxygen-dependent processes is important, as the establishment of a complex interaction between oxidative stress, oxidative protein damage and the body's antioxidant system makes it possible to clarify metabolic pathways of disease pathogenesis. In our study, we concluded that in patients with chronic non-specific inflammatory diseases of the genitals of men and women, the phagocytic activity of polymorphonuclear leukocytes is reduced mainly by the oxygen-dependent mechanism, and tissue - by the oxygen-independent. As an exception in patients with chlamydial infection, the phagocytic activity of tissue polymorphonuclear leukocytes was also reduced by an oxygen-dependent mechanism.
Keywords: oxidative stress; leukocytes; chronic inflammation; lipid peroxidation and proteins; mechanisms of phagocytosis